Scale-up of the Australian Fans in Training (Aussie-FIT) men’s health behaviour change program: Protocol for a randomised controlled hybrid effectiveness-implementation trial - McDonald, Matthew; Brickley, Bryce; Pavey, Toby; Smith, James; Maiorana, Andrew; McCaffrey, Tracy; Hillis, Graham; Bonson, Jason; Chih, Jun; Gupta, Himanshu; Holmes, Scarlett; Hunt, Kate; et al. (BMJ Journals, 2023)
Introduction: Improving physical activity (PA) and healthy eating is critical for primary and secondary prevention of cardiovascular disease (CVD). Behaviour change programmes delivered in sporting clubs can engage men in health behaviour change, but are rarely sustained or scaled-up post trial. Following the success of pilot studies of the Australian Fans in Training (Aussie-FIT) programme, a hybrid effectiveness-implementation trial protocol was developed. This protocol outlines methods to: (1) establish if Aussie-FIT is effective at supporting men with or at risk of CVD to sustain improvements in moderate-to-vigorous PA (primary outcome), diet and physical and psychological health and (2) examine the feasibility and utility of implementation strategies to support programme adoption, implementation and sustainment.